Sinking Suspicions - Hoklotubbe, Sara Sue (Book collections on Project MUSE., 2014)
"This third book in the Sadie Walela Mystery Series includes a diverse cast of characters weaving together a story of murder, thievery, and the toll of war on the human spirit. In her effort to restore balance to her neighbor's life, Sadie unravels much more than a murder"--